The complete chloroplast genome sequence of Goodyera schlechtendaliana in Korea (Orchidaceae) - Oh, Sang-Hun (Mitochondrial DNA B Resour, 2019)
Goodyera schlechtendaliana is a common orchid species in East Asia, providing a case to study phylogeographic structure of understory plants in warm temperate forests. Here, we present the complete chloroplast genome of the Korean G. schlechtendaliana. Its length is 153,801 bp and it has four subregions; 82,683 bp of large-single-copy and 18,048 bp of small-single-copy regions are separated by 26,535 bp of inverted repeat regions, including 133 genes (86 protein-coding genes, eight rRNAs, and 39 tRNAs). Phylogenetic analyses suggest that the chloroplast genomic data should be useful in future phylogeographic and phylogenetic studies of Goodyera.